Price Discovery and Captive Supply Implications for the Canadian Beef Industry - Ward, Clement E.; Schroeder, Ted C. (My University, 2010)
As cattle markets have transitioned from predominantly cash market sealed-bid or negotiated price discovery to more formula pricing, marketing agreements, forward contracts, and packer-owned cattle feeding, concerns about methods of price discovery for fed cattle have escalated. High levels of concentration in beef packing in Canada were exacerbated by cattle trade restrictions with the United States that limited market access and thus caused further unease with the price discovery process for fed cattle in Canada.
Keywords: Canada; Beef; Pricing; Supply; Mantadory Price Reporting; United States